Etude préliminaire de l'acide désoxyribonucléique (ADN) d'huîtres du littoral atlantique français - Gras, Marie-paule (Symposium CIEM, held in Aarhus, 9-12 july 1975, Danemark, 1975)
The mortality that decimated Portuguese oysters, C. angulata, in 1970-1971, up to 80% in most sectors, required the introduction of C. gigas oysters resistant to disease and whose reproduction proved itself to be excellent (GRAS and assoc. 1971). Artificial beds of Pacific oysters were created. Nonetheless, in some areas, there continued to be small populations of C. angulata that, mixed in with the C. gigas oysters that had been brought in, participated in reproduction. Genetic problems then arose, among which the selection of specimens and hybridisation were to be considered more specifically. There are, in fact, two cases of hybridisation. La mortalité qui décima les huîtres portugaises C. angulata, en 1970-1971 , à plus de 80% dans la plupart des secteurs, nécessita l'implantation d'huîtres C.gigas résistantes à la maladie et dont la reproduction s'est avérée excellente (GRAS et coll.1971). Des gisements artificiels d 'huîtres du Pacifique furent créés. Toutefois, dans certaines zones subsistaient de petites populations de C. angulata qui mêlées aux apports d'huîtres C.gigas, , participaient à la reproduction • Des problèmes de génétique se posèrent alors , parmi lesquels la sélection des spécimens et l'hybridation étaient à considérer plus particulièrement. Il existe en effet deux cas d'hybridation